Development of real and reactive power allocation methods for deregulated power system - Shareef, Hussain (2007)
The aim of deregulation in the electric power industry is to optimize the system welfare, by introducing competitive environment, mainly among the suppliers. Developing fair and equitable real and reactive power allocation method has been an active topic of research, particularly in the new paradigm, with many transactions taking place at any time. This thesis suggests two new methodologies to allocate real and reactive power output of individual generators to system loads and flows. Both allocation procedures presented can be used independently in deregulated power systems. It is based on current operating point of the system, computed through AC load flow program. The proposed reactive power allocation methodology adopts current tracing, instead of power tracing. Based on solved load flow and the network parameters, the method converts power injections and line flows into real and imaginary current injections and flows. These currents are then represented independently as real and imaginary current networks. Since current networks are acyclic lossless networks, proportional sharing principle and graph theory is used to trace the relationship between current sources and current sinks. From this relationship of current components of individual generators, it is possible to find reactive power contribution of each generator. This current tracing method can also be applied for real power allocation, with a few modifications. The second method is mainly applied for real power allocation. The method first clusters the system into small groups of buses. Then an appropriate conventional power flow tracing procedure is adopted to obtain the contribution factors within each cluster of buses. The choice of the chosen algorithm depends on their limitations and suitability. The advantages of the proposed methodologies are demonstrated on commonly used test systems and actual TNB 222 bus system. The proposed methodologies provide better reliability and minimize the limitations of conventional real and reactive power allocation methods.